Post-Revitalization Consumer Behavior in Gorontalo City’s Traditional Market - RACHMAT TAUFIK USMAN; RISNA SANABA; AMMI SALAMAH (Universitas Bina Mandiri Gorontalo, 2025)
Market revitalization is a strategic policy aimed at enhancing the competitiveness of traditional markets and sustaining their role in the local economy. This study aims to describe consumer characteristics and shopping behavior after the revitalization in one of Gorontalo's traditional markets. A descriptive quantitative approach with a cross-sectional design was employed. Data were collected through structured interviews with 64 consumers during shopping activities at the market in December 2025. Data analysis was conducted using descriptive statistics, including frequency distributions, percentages, and cross-tabulations. The results indicate that market revitalization was responded to differently by consumers. Most respondents reported changes in shopping behavior, particularly in shopping frequency, shopping duration, and dressing style when visiting the market, while some consumers experienced no noticeable change. Similar behavioral patterns were observed across consumer status, income levels, and residential distance. These findings suggest that market revitalization influences not only physical conditions but also consumer behavior and shopping experiences. This study provides empirical insights that may support the formulation of consumer-oriented policies for sustainable traditional market revitalization.